Simulating strongly correlated multiparticle systems in a truncated Hilbert space - Ernst, Thomas; Hallwood, David W.; Gulliksen, Jake; Meyer, Hans-Dieter; Brand, Joachim (Physical review. A, Atomic, molecular, and optical physics, 2011)
Representing a strongly interacting multiparticle wave function in a finite product basis leads to errors. Simple rescaling of the contact interaction can preserve the low-lying energy spectrum and long-wavelength structure of wave functions in one-dimensional systems and thus correct for the basis set truncation error. The analytic form of the rescaling is found for a two-particle system where the rescaling is exact. A detailed comparison between finite Hilbert space calculations and exact results for up to five particles show that rescaling can significantly improve the accuracy of numerical calculations in various external potentials. In addition to ground-state energies, the low-lying excitation spectrum, density profile, and correlation functions are studied. The results give a promising outlook for numerical simulations of trapped ultracold atoms.
Gesehen am 02.05.2022